Kemampuan Menganalisis berpikir tingkat tinggi Melalui Pembelajaran Berbasis Kontekstual Pada Materi Elastisitas dan hukum hooke - Pradana, Mischa Manda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of this research is to find out the application of contectualbased learning in train ability to analyze higher order thingking skill. The researchdesign is Quasy Experimental with intact group comparison design. The subjects isstudent of X MIA grade MUTUAL senior high school, where X MIA 1 as experimentclass with 24 student and X MIA2 as control class with 24 student. The data will beanalyze by descriptive analysis technique by looking at the learning result of student’sphysics concept understanding using the criteria of absortion and inferensial analysis.For the result, the student average absorption is 73.96% for experiment class and67.36% for control class. Meanwhile, inferensial analysis get 2.248 is count of t and2.202 is table of t. then, there is a difference between experiment class and controlclass. Then, it can be concluded is contectual based learning can train ability toanalyze higher order thingking skill on the lessons elastic and hooke’s lawKey word: Ability Of Higher Order Thingking Skill, Contectual, Understanding Of Concept